Evaluating Trust in Blockchain Technology for Waqf Adoption: Insights from Importance-Performance Map Analysis - Mokthar, Mohammad Zulfakhairi; Sapuan, Noraina Mazuin; Safian, Sharul Shahida Shakrein (Information Management and Business Review, 2024)
Blockchain technology offers transformative benefits for waqf by enhancing transparency, security, and efficiency. Its decentralized ledger system allows for independent transaction verification, reduces central authority risks, and improves accountability. However, while the potential benefits are significant, the success of blockchain-based waqf initiatives hinges on the level of trust that stakeholders place in this technology. Therefore, the study aims to examine the effect of trust in blockchain technology on the intention to adopt waqf blockchain with insight from importance-performance map analysis to better understand the relations between trust and intention. The study adopted a survey research design and data was collected through questionnaires distributed throughout Malaysia. The collected data were then analyzed using Smart-PLS software. The results of the analysis indicate a strong positive relationship between trust in blockchain technology and the intention to adopt waqf blockchain. However, the importance-performance map analysis shows a critical disparity exists between user expectations and actual performance, especially regarding the transaction process, which scored the lowest in performance. This implies a need to focus on improving the transaction process to align with user expectations.